Efeitos do Ziclague na espasticidade: melhora na funcionalidade e cinemática da marcha - Formighieri, Renata; Chiarani, Bruna (My University, 2019)
Introduction: Multiple Sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system. The spasticity present in these patients can limit the functionality, gait, and quality of life, for this reason, its reduction is fundamental. The Ziclague, deriving from the Alpinia Zerumbet oil, is used in muscle relaxation and tonus normalization. Objective: Measure immediate and long term effects of the Ziclague on the linear and angular variables of gait, and the functionality on a patient with MS. Methods: Pilot intervention study on a person with spasticity and limitations on the gait. Results: The measurement of muscle tone showed decrease of the spasticity in the hip adductors bilaterally, hamstrings, and plantiflexors on the right, as well as increase of the muscle strength in the hip adductors and plantiflexors. The gait analysis showed improvement in all the linear and angular kinematic parameters after the application of the Ziclague, with emphasis on the steps 1 to 5. Regarding quality of life, an improvement was observed in the fields: functional capacity, limitation by physical aspects, pain, social aspects, and mental health. In the fatigue evaluation, there was no difference in the total score. Conclusion: The Ziclague was effective in the modulation of the spastic tonus, proving its immediate and long term effect. There was an improvement in the gait kinematics, resulting from the greater muscle recruitment acquired, and in the quality of life. [resumo fornecido pelos autores]
Effects of Ziclague on spasticity: improvement in functionality abd kinematics gait
Efectos del Ziclague en la espasticidad: mejora en la funcionalidad y cinemática de la marcha
Introdução: A Esclerose Múltipla (EM) é uma patologia inflamatória desmielinizante do sistema nervoso central. A espasticidade, presente nesses pacientes, pode limitar a funcionalidade, marcha e a qualidade de vida, sendo fundamental sua redução. O Ziclague, oriundo do óleo da Alpinia Zerumbet, é utilizado no relaxamento muscular e normalização do tônus. Objetivo: Avaliar efeitos imediatos e à longo prazo do Ziclague sobre as variáveis lineares e angulares da marcha e a funcionalidade em um paciente portador de EM. Métodos: Estudo interventivo piloto com um indivíduo espástico e com limitações na marcha. A pesquisa foi desenvolvida durante 7 meses, dividida em 6 etapas, onde foi avaliado força e tônus muscular, a cinemática da marcha e o impacto na qualidade de vida e fadiga. Resultados: A avaliação do tônus muscular demonstrou diminuição da espasticidade em adutores de quadril bilateralmente, isquiotibiais e plantiflexores à direita, bem como o aumento da força muscular em adutores de quadris e plantiflexores. A análise da marcha demonstrou melhora em todos os parâmetros cinemáticos lineares e angulares após aplicação do Ziclague, tendo ênfase nas etapas 1 a 5. Em relação a qualidade de vida, observou-se melhora nos domínios capacidade funcional, limitação por aspectos físicos, dor, aspectos sociais e saúde mental. Na avaliação da fadiga, não houve diferença no escore total. Conclusão: O Ziclague foi eficaz na modulação do tônus espástico, comprovando seu efeito imediato e à longo prazo. Houve uma melhora na cinemática da marcha, advinda do maior recrutamento muscular adquirido, e na qualidade de vida. [resumo fornecido pelos autores]
Keywords: Espasticidade muscular; Esclerose múltipla